Percutaneous aortopulmonary window closure using muscular ventricular septal defect occluder. Instituto Nacional de Salud del Niño San Borja Lima- Perú. Case Report - Catalán Cabrera, Alex Ismael (2025)
The aortopulmonary window is a rare congenital heart defect, and the aortopulmonary window without other associated defects represents up to 25% of these defects. Surgical closure has been and is the gold standard in many cardiovascular centers. However, percutaneous closure is being performed with different types of occluders, considering the type of defect, size, and edges in order to avoid complications such as valvular or coronary ostial involvement. We present the case of an infant with an aortopulmonary window who underwent percutaneous closure with a muscular ventricular septal defect occluder device without complications and was discharged 48 hours after the procedure.